Glagoljaši u Splitu u 15. stoljeću - Runje, Petar (2020)
U članku se iznose podaci pronađeni u bilježničkim spisima iz 15. stoljeća o knjizi na hrvatskom jeziku u osobnoj knjižnici splitskoga arhiprezbitera i o nekim svećenicima glagoljašima tada nastanjenima u gradu Splitu. Posebno je značenje tih podataka u tome što neki drugi iz srednjega vijeka koji bi svjedočili o nazočnosti i djelovanju glagoljaša u samom sjedištu Splitske nadbiskupije, nisu do sada pronađeni.
The author emphasizes the fact that the historians so far have not discovered written traces of the presence and activities of Glagolitic priests in the centuries of the Middle Ages in the city of Split, although some traces from the area of the Archdiocese of Split have long been known. Therefore, rare information found in the writings of the 15th century is a valuable historical testimony. In this paper, they are recorded and carefully explained. There is an interesting and at least somewhat justifiable assumption about the connection between the Glagolitic priests from the area of present-day western Bosnia and Split and the area of the Archdiocese of Split.
Bibliografske bilješke uz tekst.
Sažetak ; Summary.
Keywords: Glagoljaši -- Bilježnički spisi; 15. st; Split